The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1159/000495925
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a DNA Aptamer for Ovarian Cancer Clinical Tissue Recognition and in Vivo Imaging

Abstract: Backgrounds/Aims: Ovarian cancer is the most lethal gynaecologic malignancy and is difficult to detect early. The inefficient early diagnosis of ovarian cancer is the main contributor to its high mortality rate. Aptamers, as chemical antibodies, are single-stranded DNA or RNA oligonucleotides that target cells or molecules with high affinity. Methods: Binding ability of R13 was measured by flow cytometry analysis. Stability of R13 was tested in blood serum of an ovarian cancer patient. Internalization of R13 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…A number of aptamers have been designated for various diseases, eg, types of cancers. 21,22 Table 1 describes a list of the most common differences between an antibody and aptamer.…”
Section: Introductionmentioning
confidence: 99%
“…A number of aptamers have been designated for various diseases, eg, types of cancers. 21,22 Table 1 describes a list of the most common differences between an antibody and aptamer.…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancer is one of the most lethal gynecologic tumors that are not easy to be detected at an early stage, which contributes to a high mortality rate. In a clinical study of ovarian cancer patients, the affinity of R13 aptamer with cancer cells was studied through flow cytometry analysis [ 47 ]. Additionally, the stability of R13 aptamer was also analyzed in an ovarian cancer patient’s blood serum.…”
Section: Aptamers In Cancer Diagnosismentioning
confidence: 99%
“… Zhu et al (2017) labeled the screened aptamers Heraptamer 1 and Heraptamer 2 with isotope 18 F, followed by PET imaging in a mouse model of ovarian cancer induced by SKOV3 cells, which exhibited high signal-to-background ratios within a short time and prevented aptamer degradation by nucleases. Li et al (2018) injected Cy5-labeled R13 aptamer into nude mice and performed fluorescent imaging for tumor and organs half an hour later. A weak fluorescent signal was obtained in the first 1.5 h, which peaked at 3.5 h, and lasted for 9.5 h. Zhu et al (2017) and Li et al (2018) demonstrated the feasibility of using aptamers for in vivo imaging and suggested more approaches for ovarian cancer diagnosis.…”
Section: Applications Of Aptamers In Ovarian Cancer Diagnosismentioning
confidence: 99%